Risk Aversion and Hydro-energy Reservoirs Management under Monopolistic and Oligopolistic Industrial Structures - Abbassi, Abdessalem; Dakhlaoui, Ahlem; Khalifa, Nihed Ben (International Journal of Energy Economics and Policy, 2023)
This article analyses management of hydropower dams within monopolistic and oligopolistic competition and when hydroelectricity producers are risk averse and face demand uncertainty. In each type of market structure we analytically determine the water release path at the closed-loop equilibrium. In the monopolistic case, we demonstrate that intertemporal allocation of hydro resources is done by additional pumping or storage depending on the relative abundance of water between different regions in order both to internalize the risk and to smooth the effect of uncertainty on electricity prices. In the oligopolistic case, we determine the conditions under which the relative scarcity (abundance) of water in the dam of a hydroelectric operator can favor additional strategic pumping (storage) in its competitor’s dams. Finally, we compare the effects of risk aversion on the output industry. We show, in monopolistic case, that the greater the generators’ risk aversion the larger the current water storage for future demands. In the oligopolistic case, however, the risk aversion increasing may be either in favor of reducing or increasing the total hydro output depending on demand uncertainty and market power parameters. We deduce that risk aversion coupled with market power may induce, under some condition, a misallocation of hydraulic resource across time.